2018
DOI: 10.2147/ppa.s159621
|View full text |Cite
|
Sign up to set email alerts
|

Complex interrelations between self-reported oral health attitudes and behaviors, the oral health status, and oral health-related quality of life

Abstract: PurposeThe purpose of this study was to develop and test a moderated mediation model that was able to describe the relationships between oral health-related attitudes and behaviors, oral health status (OHS), and oral health-related quality of life. The hypothesized relations corresponded to research questions such as “is a person’s oral health predicted by the actions that person takes in order to prevent oral health conditions?” and “do individuals with better oral health also have higher levels of oral healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…The HU-DBI was originally designed in Japanese, and was later translated into English and many other languages. The reliability of the scale was confirmed by previous studies [18][19][20] . In our research, we used the Croatian version of HU-DBI, which has already been used in previous studies 21 .…”
Section: Methodssupporting
confidence: 78%
“…The HU-DBI was originally designed in Japanese, and was later translated into English and many other languages. The reliability of the scale was confirmed by previous studies [18][19][20] . In our research, we used the Croatian version of HU-DBI, which has already been used in previous studies 21 .…”
Section: Methodssupporting
confidence: 78%
“…Oral health status is usually ignored when global health status of an individual is taken under consideration [ 5 ]. Interest in the effect of oral health on the prevention of systemic disease has gained importance in recent years with researchers recognizing the bi-directional relationship between both of them [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that oral health behaviours have a negative impact on OHRQoL. However, Vigu AL et al 's study of Romanian college students found a association between oral behaviours and OHRQoL [57].…”
Section: Discussionmentioning
confidence: 87%
“…The results indicated that oral health behaviours have a negative impact on OHRQoL. However, Vigu AL et al 's study of Romanian college students found a association between oral behaviours and OHRQoL [57]. A study by Broadbent et al found that oral health behaviours in adults have a signi cant impact on symptoms such as dental caries or tooth loss, thus further in uencing OHRQoL [29].…”
Section: Discussionmentioning
confidence: 97%